sj-pdf-1-wso-10.1177_17474930211040720 - Supplemental material for Cerebrovascular disease at young age is related to mother’s health during the pregnancy—The Northern Finland Birth Cohort 1966 study ... - Rissanen, Ina; Geerlings, Mirjam I; Juvela, Seppo; Miettunen, Jouko; Paananen, Markus; Tetri, Sami (SAGE Journals, 2021)
Supplemental material, sj-pdf-1-wso-10.1177_17474930211040720 for Cerebrovascular disease at young age is related to mother’s health during the pregnancy—The Northern Finland Birth Cohort 1966 study by Ina Rissanen, Mirjam I Geerlings, Seppo Juvela, Jouko Miettunen, Markus Paananen and Sami Tetri in International Journal of Stroke ...